2010
DOI: 10.1128/iai.00461-10
|View full text |Cite
|
Sign up to set email alerts
|

Development of Two Animal Models To Study the Function of Vibrio parahaemolyticus Type III Secretion Systems

Abstract: Vibrio parahaemolyticus is an emerging food-and waterborne pathogen that encodes two type III secretion systems (T3SSs). Previous studies have linked type III secretion system 1 (T3SS1) to cytotoxicity and T3SS2 to intestinal fluid accumulation, but animal challenge models needed to study these phenomena are limited. In this study we evaluated the roles of the T3SSs during infection using two novel animal models: a model in which piglets were inoculated orogastrically and a model in which mice were inoculated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
65
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 36 publications
0
65
0
Order By: Relevance
“…T3SS-2 plays only a minor role in cytotoxicity but is the major contributing factor toward enterotoxicity (17,22,23,27). Studies have demonstrated that fluid accumulation in the rabbit ileal loop model as well as virulence in the infant rabbit and infant pig models are dependent upon a functional 22,23,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…T3SS-2 plays only a minor role in cytotoxicity but is the major contributing factor toward enterotoxicity (17,22,23,27). Studies have demonstrated that fluid accumulation in the rabbit ileal loop model as well as virulence in the infant rabbit and infant pig models are dependent upon a functional 22,23,27).…”
mentioning
confidence: 99%
“…The T3SS-2 gene cluster is flanked by a copy of the tdh gene (tdhA and tdhS) within an 80-kb pathogenicity island named VPaI-7, a region found only in clinical isolates (16,(24)(25)(26). T3SS-2 plays only a minor role in cytotoxicity but is the major contributing factor toward enterotoxicity (17,22,23,27). Studies have demonstrated that fluid accumulation in the rabbit ileal loop model as well as virulence in the infant rabbit and infant pig models are dependent upon a functional T3SS-2 (17,22,23,27).…”
mentioning
confidence: 99%
“…More recently, a third gene cluster, encoding a T3SS, has been identified in a tdh-negative, trh-positive V. parahaemolyticus strain (56). Several functional T3SS effector proteins have been identified (2,21,34,45,60,65,76), including the T3SS-1 effectors VopQ (VP1680), VopR (VP1683), VopS (VP1686), VP1659, and VPA0450. It has been found that the production of these effector proteins by V. parahaemolyticus induces autophagy, cell rounding, cell lysis, and cell death in vitro in a variety of different eukaryotic cell types (7-9, 36, 39, 76).…”
mentioning
confidence: 99%
“…It has been found that the production of these effector proteins by V. parahaemolyticus induces autophagy, cell rounding, cell lysis, and cell death in vitro in a variety of different eukaryotic cell types (7-9, 36, 39, 76). Each T3SS in V. parahaemolyticus has been shown to be functional, although data suggest that the contribution of each to virulence differs markedly (21,61,65,85). The regulation of the T3SS-1 system was shown to fall under the control of the ExsACDE system, with ExsA and ExsD acting as positive and negative regulators of T3SS-1 gene expression, respectively.…”
mentioning
confidence: 99%
“…T3SS1 appeared to be responsible for the cytotoxicity to several mammalian cell lines (Burdette et al, 2008;Hiyoshi et al, 2010;Nydam et al, 2014;Zhou et al, 2009) and mortality in a mouse model Pineyro et al, 2010).…”
Section: Impact Of Nascent and Residual Rna On Virulence Gene Expressmentioning
confidence: 99%